Efficacy of Stiripentol Beyond Dravet Syndrome: A Retrospective Medical Record Review of Patients with Drug-Resistant Epilepsies - Víctor Soto-Insuga; Elena González-Alguacil; María Ballarà-Petitbò; Nuria Lamagrande-Casanova; Anna Duat-Rodríguez; Cristina Benítez-Provedo; Elena Cardenal-Muñoz; Juan José García-Peñas (Neurology and Therapy)
Abstract Introduction Stiripentol is approved as an add-on therapy with clobazam and/or valproate for seizures associated with Dravet syndrome (DS). Evidence of stiripentol efficacy in other drug-resistant epilepsies is limited. Methods This was a single-centre, retrospective, observational study of patients aged ≤ 15 years with non-Dravet epilepsy or DS who initiated stiripentol treatment in Spain. Results The study included 18 patients with DS and 17 with non-Dravet epilepsy; 76.5% of the latter had a developmental and epileptic encephalopathy. Median (range) age at stiripentol initiation was 52 (4–180) months. Three months of add-on stiripentol provided overall improvement in seizures (number, duration and/or intensity) for 76.5% of the non-Dravet and 61.1% of the DS patients (p = 0.30), all of whom were drug-resistant to prior antiseizure medications (ASMs). Stiripentol reduced seizure frequency by ≥ 50% in 58.8% of the non-Dravet patients and 44.4% of the DS cohort (p = 0.40); 20% of all patients became seizure-free. Stiripentol reduced all seizure types in both cohorts. Kaplan–Meier survival analysis found a higher probability of sustained stiripentol efficacy in the DS cohort (120 months) than the non-Dravet cohort (16 months; p = 0.012). Stiripentol improved cognition and Clinical Global Impression scale scores in approximately 60% of all patients; sleep improved for 19.2%. Acute stiripentol treatment (maximum dose 6.7–100 mg/kg/day) initiated in five patients (four with non-Dravet epilepsy and one with DS) during refractory status epilepticus (SE) successfully resolved SE over a median 0.5 days. Adverse events, mainly mild-to-moderate, occurred in 47.1% and 41.2% of patients in the non-Dravet and DS cohorts, respectively. Six patients (35.3%) with non-Dravet epilepsy discontinued ≥ 1 other ASMs after stiripentol initiation. Conclusion Add-on stiripentol provides overall improvement in different seizure types and non-seizure manifestations for paediatric patients with drug-resistant epilepsy, including epileptic syndromes besides DS, and appeared effective in acute treatment of SE. Stiripentol was generally well tolerated.